Coagulation Profile Changes Due to Thromboprophylaxis and Platelets in Trauma Patients at High-Risk for Venous Thromboembolism. Issue 7 (July 2015) - Allen, Casey J.; Murray, Clark R.; Meizoso, Jonathan P.; Ray, Juliet J.; Teisch, Laura F.; Ruiz, Xiomara D.; Hanna, Mena M.; Guarch, Gerardo A.; Manning, Ronald J.; Livingstone, Alan S.; Ginzburg, Enrique; Schulman, Carl I.; et al.
We hypothesize there are coagulation profile changes associated both with initiation of thromboporphylaxis (TPX) and with change in platelet levels in trauma patients at high-risk for venous thromboembolism (VTE). A total of 1203 trauma intensive care unit patients were screened with a VTE risk assessment profile. In all, 302 high-risk patients (risk assessment profile score ≥ 10) were consented for weekly thromboelastography. TPX was initiated between initial and follow-up thromboelastography. Seventy-four patients were analyzed. Upon admission, 87 per cent were hypercoagulable, and 81 per cent remained hypercoagulable by Day 7 ( P = 0.504). TPX was initiated 3.4 ± 1.4 days after admission; 68 per cent received unfractionated heparin and 32 per cent received low-molecular-weight heparin. The VTE rate was 18 per cent, length of stay 38 (25–37) days, and mortality of 17.6 per cent. In all, 76 per cent had a rapid clotting time at admission versus 39 per cent at Day 7 ( P < 0.001); correcting from 7.75 (6.45–8.90) minutes to 10.45 (7.90–15.25) minutes ( P < 0.001). At admission, 41 per cent had an elevated maximum clot formation (MCF) and 85 per cent had at Day 7 ( P < 0.001); increasing from 61(55–65) mm to 75(69–80) mm ( P < 0.001). Platelets positively correlated with MCF at admission (r = 0.308, R 2 = 0.095, P = 0.008) and at Day 7 (r = 0.516, R 2 = 0.266, P < 0.001). Change in platelet levels correlated with change in MCF (r = 0.332, R 2 = 0.110, P = 0.005). In conclusion, hypercoagulability persists despite the use of TPX. Although clotting time normalizes, MCF increases in correlation with platelet levels. As platelet function is a dominant contributor to sustained trauma-evoked hypercoagulability, antiplatelet therapy may be indicated in the management of severely injured trauma patients.